A Nosocomial Respiratory Infection Outbreak of Carbapenem-Resistant Escherichia coli ST131 With Multiple Transmissible blaKPC–2 Carrying Plasmids - Gong, Lin; Tang, Na; Chen, Dongke; Sun, Kaiwen; Lan, Ruiting; Zhang, Wen; Zhou, Haijian; Yuan, Min; Chen, Xia; Zhao, Xiaofei; Che, Jie; Bai, Xuemei; et al. (Frontiers in Microbiology, 2020)
Escherichia coli sequence type 131 (ST131) is well known for its multidrug resistance profile. Carbapenems have been considered the treatment of choice for E. coli ST131 infections and resistance to carbapenems is now emerging due to the acquisition of carbapenemase. 45 carbapenem-resistant E. coli isolates were collected in a hospital. The resistance mechanisms, plasmid profiles and genetic relatedness of these strains were determined. Phylogenetic relationships between these strains were assessed by molecular profiling and aligned with patient clinical details. The genetic context of blaKPC-2 was analyzed to trace the potential dissemination of blaKPC-2.45 carbapenem-resistant E. coli ST131strains are closely related. Initially prevalent only in the ward E02, ST131 subsequently spread to other wards and multiple lineages evolved independently, resulting in a respiratory infection outbreak of carbapenem-resistant E. coli ST131. Eight of the 30 patients died within 28 days of the first E. coli ST131 isolation. The blaKPC-2 positive plasmid profiles suggest that the carbapenem resistance was due to the acquisition of transmissible plasmids pE0272_KPC and pE0171_KPC carrying blaKPC-2 by E. coli ST131. Additionally, diverse multidrug resistance elements were transferred and rearranged between these plasmids mediated by IS26. E. coli ST131 has become a multidrug resistant epidemic clone that can cause hospital-acquired respiratory infections resulting in mortality. Our research indicates that clinical attention should be paid to the importance of E. coli ST131 in respiratory infections. The emergence of blaKPC in E. coli ST131 may herald the beginning of the high prevalence of carbapenem resistance in Chinese communities and hospitals.